Switching to online learning: Using the flipped learning approach to deliver pre-sessional EAP remotely - Hudson, Jolanta (GILE Journal of Skills Development, 2022)
This small-scale study investigates how the flipped approach to learning helped a UK university teaching team deliver the Pre-sessional English for Academic Purposes (EAP) course remotely during the pandemic. The study draws on the theoretical framework of the flipped approach to learning to explore the use of the approach in the Higher Education (HE) context. The study suggests that the flipped approach to learning may be helpful in the delivery of pre-sessional EAP courses remotely as it offers students opportunities to engage in communicative activities and encourages independent learning and autonomy, both of which are key practices in EAP. However, teachers may find the approach challenging if they cannot monitor students’ work or connect with them while completing the flipped activities. Only a few studies have focused on this issue to date. Further research involving more teachers and students is recommended to provide additional insights on this aspect of teaching remotely.